IL‐17 drives salivary gland dysfunction via inhibiting TRPC1‐mediated calcium movement in Sjögren's syndrome. Issue 4 (29th April 2021) - Xiao, Fan; Du, Wenhan; Zhu, Xiaoxia; Tang, Yuan; Liu, Lixiong; Huang, Enyu; Deng, Chong; Luo, Cainan; Han, Man; Chen, Ping; Ding, Liping; Hong, Xiaoping; et al.
Abstract: Objectives: This study aims to determine a role of interleukin‐17A (IL‐17) in salivary gland (SG) dysfunction and therapeutic effects of targeting IL‐17 in SG for treating autoimmune sialadenitis in primary Sjögren's syndrome (pSS). Methods: Salivary IL‐17 levels and IL‐17‐secreting cells in labial glands of pSS patients were examined. Kinetic changes of IL‐17‐producing cells in SG from mice with experimental Sjögren's syndrome (ESS) were analysed. To determine a role of IL‐17 in salivary secretion, IL‐17‐deficient mice and constructed chimeric mice with IL‐17 receptor C (IL‐17RC) deficiency in non‐hematopoietic and hematopoietic cells were examined for saliva flow rates during ESS development. Both human and murine primary SG epithelial cells were treated with IL‐17 for measuring cholinergic activation‐induced calcium movement. Moreover, SG functions were assessed in ESS mice with salivary retrograde cannulation of IL‐17 neutralisation antibodies. Results: Increased salivary IL‐17 levels were negatively correlated with saliva flow rates in pSS patients. Both IL‐17‐deficient mice and chimeric mice with non‐hematopoietic cell‐restricted IL‐17RC deficiency exhibited no obvious salivary reduction while chimeric mice with hematopoietic cell‐restricted IL‐17RC deficiency showed significantly decreased saliva secretion during ESS development. In SG epithelial cells, IL‐17 inhibited acetylcholine‐induced calcium movement and downregulated the expression of transient receptor potential canonical 1 via promoting Nfkbiz mRNA stabilisation. Moreover, local IL‐17 neutralisation in SG markedly attenuated hyposalivation and ameliorated tissue inflammation in ESS mice. Conclusion: These findings identify a novel function of IL‐17 in driving salivary dysfunction during pSS development and may provide a new therapeutic strategy for targeting SG dysfunction in pSS patients. Abstract : In this study, we found that increased salivary IL‐17 levels were negatively correlated with saliva flow rates in patients with primary Sjögren's syndrome (pSS). We further identified a novel function of IL‐17 in driving salivary dysfunction by impairing transient receptor potential canonical 1‐mediated calcium movement during pSS pathogenesis. This pre‐clinical study demonstrated that neutralization of IL‐17 in salivary glands attenuated hyposalivation and ameliorated tissue inflammation in mice with experimental SS, suggesting a therapeutic potential of local targeting IL‐17 for treating xerostomia and autoimmune sialadenitis in pSS patients.